(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study aimed to identify the impact of financial decisions and their degree of transparency on institutional growth, focusing on Al Rajhi Bank in Saudi Arabia. It also sought to clarify the meaning of financial decisions, institutional growth, and related theoretical concepts, and to analyze the impact of Al Rajhi Bank’s financing decisions on its financial growth and sustainability within the Saudi banking market. The study employed a descriptive-analytical approach, deemed the most suitable for the research topic. The study concluded that financial decisions (financing, investment, and profit distribution) collectively have a statistically significant impact on Al Rajhi Bank’s internal and external growth. Regression analysis revealed that financial decisions explain 59.2% of the variance in internal growth, reflecting a moderate to strong effect. The results further indicated that financing decisions have a significant positive impact on internal growth, demonstrating their role in improving operational efficiency.